THE FORMATION AND SOURCES OF NEOLOGISMS IN MODERN UZBEK AND ENGLISH LEXICONS - Ruzmuratova Aziza Anvarovna (Modern American Journals, 2025)
This article examines the nature, formation, and sources of neologisms in modern Uzbek and English lexicons. In the twenty-first century, globalization, technological advancement, and cultural contact have dramatically increased the speed at which new words appear in different languages. English, as a global lingua franca, is highly receptive to lexical innovation, while Uzbek, as a national language undergoing modernization and standardization, demonstrates a unique balance between openness to borrowing and linguistic purism. This paper discusses the theoretical perspectives on neologism, surveys key word-formation processes, and provides comparative examples to illustrate how new words are coined, borrowed, adapted, and integrated in both languages. The study highlights how media, technology, youth culture, and institutional language planning shape the trajectory of neologism formation and adoption.
Keywords: neologism, word formation, borrowing, derivation, compounding, lexical innovation, Uzbek language, English language, linguistic policy.